Rapid antigen detection test for respiratory syncytial virus diagnosis as a diagnostic tool - Flávio da Silva Mesquita; Danielle Bruna Leal de Oliveira; Daniela Crema; Célia Miranda Nunes Pinez; Thaís Cristina Colmanetti; Luciano Matsumia Thomazelli; Alfredo Elias Gilio; Sandra Elisabeth Vieira; Marina Baquerizo Martinez; Viviane Fongaro Botosso; Edison Luiz Durigon (Brazilian Society of Pediatrics, 2017)
Objective: The aim of this study was to evaluate the QuickVue® RSV Test Kit (QUIDEL Corp, CA, USA) as a screening tool for respiratory syncytial virus in children with acute respiratory disease in comparison with the indirect immunofluorescence assay as gold standard. In Brazil, rapid antigen detection tests for respiratory syncytial virus are not routinely utilized as a diagnostic tool, except for the diagnosis of dengue and influenza. Methods: The authors retrospectively analyzed 486 nasopharyngeal aspirate samples from children under age 5 with acute respiratory infection, between December 2013 and August 2014, the samples were analyzed by IFI and QuickVue® RSV Test kit. Samples with discordant results were analyzed by RT‐qPCR and nucleotide sequencing. Results: From 313 positive samples by immunofluorescence assays, 282 (90%) were also positive by the rapid antigen detection test, two were positive only by rapid antigen detection test, 33 were positive only by immunofluorescence assays, and 171 were positive by both methods. The 35 samples with discordant results were analyzed by RT‐qPCR; the two samples positive only by rapid antigen detection test and the five positive only by immunofluorescence assays were also positive by RT‐qPCR. There was no relation between the negativity by QuickVue® RSV Test and viral load or specific strain. The QuickVue® RSV Test showed sensitivity of 90%, specificity of 98.8%, PPV of 99.3%, and negative predictive value of 94.6%, with accuracy of 93.2% and agreement κ index of 0.85 in comparison to IFA. Conclusions: This study demonstrated that the QuickVue® RSV Test Kit can be effective in early detection of Respiratory syncytial virus in nasopharyngeal aspirate and is reliable for use as a diagnostic tool in pediatrics.